Hexagonal Boron Nitride–Metal Junction: Removing the Schottky Barriers by Grain Boundary. Issue 9 (3rd July 2018) - Ding, Junfei; Ahmed, Dildar; Sun, Huasheng; Chen, Shanbao; Yao, Qiushi; Huang, Chengxi; Deng, Kaiming; Kan, Erjun
Abstract: Atomically thin hexagonal boron nitride (h‐BN) layers have been used as an ultra‐thin spacer layer for metal–insulator–metal (MIM) structures, which enables a wide range of applications such as nanocapacitors and field‐effect tunneling transistors. Although pristine h‐BN layers, produced by chemical vapor deposition (CVD) methods, are always with ubiquitous grain boundaries (GBs), the contact of such layers with transition metal (TM) has not been explored. Here, we studied h‐BN monolayer with GBs on Ni(111) and Cu(111) surfaces through a comprehensively first‐principles calculation. Our results show that for the free‐standing h‐BN monolayer with GBs, it presents a moiré pattern characteristic and its energy gap is narrowed by about 38%. When h‐BN with GBs is deposited on Ni(111) and Cu(111) surfaces, the GBs containing B‐B pairs are attracted to the TM surface while the GBs with N‐N pairs(GBs‐N) parts are repelled from the surfaces. Interestingly, the calculated Schottky barriers (SBs) for electrons between the h‐BN layer and the TM surfaces almost disappear due to the existence of GB structures. Thus, our results predicted that h‐BN with GBs may form ohmic contact with TM surfaces, which can be used in real electric devices. Abstract : When h‐BN with GBs is deposited on Ni(111) and Cu(111) surfaces, the GBs containing B‐B pairs are attracted to the TM surface. The calculated Schottky barriers (SBs) for electrons between the h‐BN layer and the TM surfaces almost disappear due to the existence of GB structures.